ROLE OF HYSTERORESECTOSCOPY IN DIAGNOSING AND TREATMENT OF INFERTILITY DUE TO ENDOMETRIAL PATHOLOGY - Sharipova, Sh.O.; Burxonova, S.B.; Solieva, Z.F.; Gafurova, E.O. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. Among the causes of infertility associated with endometrial pathology, synechiae and polyps occupy a leading position. Endoscopic surgery in the treatment of women with endometrial pathology of reproductive age is considered to be a method of organ preservation. The purpose of the study consists in studying the possibilities of hysteroresectoscopy in the diagnosis and treatment of infertile women associated with endometrial pathology. Materials. 80 infertile women were included in the study. The main group included 26 women (group I) with endometrial synechiae and 34 women with endometrial polyps (group II). The control group was made up of 20 healthy women. All patients underwent clinical laboratory, histomorphological and instrumental examinations. Results. 26 women with endometrial synechia underwent adhesiolysis using hysteroresectoscopy, and 34 women underwent polypectomy. The use of hysteroresectoscopy helps to identify the causes of infertility at the same time as eliminating them, which led to pregnancy in 83.4% of infertile women due to endometrial pathology. Conclusion. The use of hysteroresectoscopic surgical technologies in the diagnosis and treatment of endometrial pathologies leads to the elimination of infertile women and the restoration of fertility in 83.4% of them. The use of hysteroresectoscopy in the diagnosis and treatment of endometrial pathologies leads to a 2.1-fold (83.4%) increase in the pregnancy rate of infertile women associated with these pathologies.